Multifunctional probiotic and safety attributes Heyndrickxia coagulans isolated from stingless bee honey - Benyapa Prakit; Rungravee Chaiyod; Kittiya Khongkool; Wankuson Chanasit; Monthon Lertworapreecha (Annals of Microbiology, 2025)
Abstract Background Heyndrickxia coagulans, recognized for its probiotic attributes and resilience as an endospore-forming bacterium, is increasingly studied for health supplement applications. This study aimed to evaluate the probiotic potential and safety of novel H. coagulans isolated from stingless bee honey, a new source for this bacterium, and to characterize their multifunctional probiotic properties. Results We isolated two novel H. coagulans, TBRC-18260 and TBRC-18261, and conducted comprehensive in vitro analyses to assess their probiotic traits such as acid and bile salt tolerance, self-aggregation, and pathogen inhibition. Both isolates were also evaluated for safety through antibiotic susceptibility testing and hemolytic activity. Functional properties, including GABA production, antioxidant activity, were examined to establish their potential as probiotics. TBRC-18260 and TBRC-18261 exhibited core probiotic characteristics and showed excellent survivability under acidic conditions and in the presence of bile salts. They displayed strong antimicrobial activity against various pathogens and demonstrated significant GABA production and antioxidant capabilities. The safety assessments confirmed their non-hemolytic nature and susceptibility to a wide range of antibiotics. Conclusion The novel H. coagulans isolates, TBRC-18260 and TBRC-18261, with their robust probiotic properties, antioxidant activities, and safety profiles, emerged as promising candidates for the development of functional foods and dietary supplements. This study enhances the biodiversity of available probiotics and supports the continuous search for novel strains with unique health-promoting characteristics.